Comparative Analysis of Geo-Electric Anomaly Definition Using Three Conventional Arrays A Near Subsurface Investigation in the University of Ghana, Legon. - Renner, S (University of Ghana, 2015)
Complexity in the near subsurface affects resistivity distribution such that arrays can produce different representations of the same subsurface structure. Comparison and analysis have been presented for the performance of three conventional resistivity arrays -Wenner, Schlumberger, and dipole-dipole - with respect to their ability to resolve anomaly in the ‗very‘ near subsurface. Assessment was on the definition of naturally-occurring anomaly - resistivity lows associated with borehole positions - in varying environment, and definition of artificial anomalies of fixed and undefined geometries - buried salt unit and leachate saturated zone – in a more laterally inhomogeneous setting of a dumpsite. This was with respect to the ability of the individual arrays to successfully resolve the lateral and vertical resistivity variation in the sub-environments and in the process, delineate the related anomaly. Maximum depth of investigation was about 5 m. Profile plots for the various arrays along the same traverse showed varying similarities with no two patterns being the same. The Wenner array performed best in imaging the buried salt unit followed by the Schlumberger array, which defined the unit better in the pseudo-section. The dipole-dipole array did not image the salt unit, in both the pseudo- and true resistivity section. The Wenner and Schlumberger arrays also showed better imaging of zones with undefined geometry and showed a high level of consistency in image and profile pattern similarities. The dipole-dipole array was for most part non-conformable. These discrepancies have been attributed collectively to the individual array sensitivity, configuration and geometric factor, and profiling/sampling technique. The plots and images showed that the measure and extent of similarity between the images and the profiles of the different arrays is dependent on the simplicity of the subsurface resistivity distribution and structure.
Keywords: COMPARATIVE ANALYSIS; GEO-ELECTRIC ANOMALY; DEFINITION; CONVENTIONAL; ARRAYS; NEAR SUBSURFACE; INVESTIGATION; UNIVERSITY OF GHANA